Aluminium hydroxide impregnated macroreticular aromatic polymeric resin as a sustainable option for defluoridation. Issue 2 (June 2015) - Barathi, M.; Kumar, A. Santhana Krishna; Rajesh, N.
Graphical abstract: Highlights: Aluminium hydroxide impregnated macroporous polymeric adsorbent was prepared. Characterization of the adsorbent was studied in detail. The sorbent has a maximum F − ion adsorption capacity of 36.61 mg g −1 at pH 7.0. F − ion adsorption favoured by electrostatic interaction and hydrogen bonding. Adsorbent is effectively regenerated with sodium hydroxide. Abstract: The purpose of the present study was to explore the potential application of aluminium hydroxide impregnated macroporous polymeric resin as a sustainable option for fluoride removal from aqueous solution. Electrostatic interaction between fluoride and the cationic metal hydroxide as well as hydrogen bonding (metal-OH⋯F) could be inferred through Fourier transform infrared spectroscopy (FT-IR), X-ray diffraction (XRD), scanning electron microscopy (SEM) and energy dispersive X-ray spectroscopy (EDS) techniques. This macroreticular adsorbent gave a high adsorption capacity (92.39 and 36.61 mg g −1 at pH 3.0 and 7.0) by fitting the experimental data with the nonlinear Langmuir isotherm model. The pseudo-second-order adsorption process could be described using surface and intraparticle diffusion. Thermodynamics of adsorption accounted for the spontaneity and exothermic interaction with a corresponding decrease in entropy. The Al(OH)3 impregnated polymeric resin adsorbent was tested with 5 mg L −1 fluoride and its efficacy was demonstrated in a laboratory scale column study. The resin exhibits good potential towards practical applications for the remediation of fluoride.